Transformasi Digital Widyaiswara: Analisis Interaksi Publikasi Ilmiah dan Pemanfaatan Teknologi Digital - Rahman, Alpha Fadila Juliana; Kamaliah, Naily; Sukoco, Sutrisno Heru (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
This study examines the role of widyaiswara in research activities, specifically the usage of digital literacy and artificial intelligence (AI) in scientific publications. Using descriptive and inferential analysis (Fisher Exact Test and Dummy regression), it was discovered that 87.5% of respondents had participated in scientific publications, with 65% serving as main authors, whereas 7.5% had never written. As many as 81.25% of widyaiswara perform scientific searches, while just 34.38% use reference management tools. The Fisher test revealed a substantial correlation between publication type and scientific search utilization, but not with reference management systems. The usage of AI in publications remains minimal, with just 16.1% of respondents using it, and there is no meaningful association with publication type. Regression models suggest that digital literacy considerably increases the number of scientific publications, but AI has not been widely used. Overall, widyaiswara's level of technology use and digital literacy remains poor when it comes to publishing scientific articles in the digital era. Keywords: Widyaiswara; Digital Transformation; Scientific Publication; Digital Literacy; Artificial Intelligence (AI)